2017
DOI: 10.7554/elife.26980
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic lethality between the cohesin subunits STAG1 and STAG2 in diverse cancer contexts

Abstract: Recent genome analyses have identified recurrent mutations in the cohesin complex in a wide range of human cancers. Here we demonstrate that the most frequently mutated subunit of the cohesin complex, STAG2, displays a strong synthetic lethal interaction with its paralog STAG1. Mechanistically, STAG1 loss abrogates sister chromatid cohesion in STAG2 mutated but not in wildtype cells leading to mitotic catastrophe, defective cell division and apoptosis. STAG1 inactivation inhibits the proliferation of STAG2 mut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 44 publications
5
51
1
Order By: Relevance
“…Thus for ~13% of the paralogs with variable essentiality, their essentiality can be associated with lower expression of their most sequence similar paralog, suggesting a potential synthetic lethal relationship. These pairs include many of the synthetic lethal relationships between paralogs previously reported in the literature, including ARID1A/ARID1B [33], SMARCA2/SMARCA4 [34,35], STAG1/STAG2 [36,37], ENO1/ENO2 [38], and RPL22/RPL22L1 [39] ( Fig 5C).…”
Section: Synthetic Lethality With Variably Expressed Genes Contributementioning
confidence: 87%
See 1 more Smart Citation
“…Thus for ~13% of the paralogs with variable essentiality, their essentiality can be associated with lower expression of their most sequence similar paralog, suggesting a potential synthetic lethal relationship. These pairs include many of the synthetic lethal relationships between paralogs previously reported in the literature, including ARID1A/ARID1B [33], SMARCA2/SMARCA4 [34,35], STAG1/STAG2 [36,37], ENO1/ENO2 [38], and RPL22/RPL22L1 [39] ( Fig 5C).…”
Section: Synthetic Lethality With Variably Expressed Genes Contributementioning
confidence: 87%
“…Our findings suggest a simple approach to prioritize such paralog pairs by focusing on whole genome duplicates coding for subunits of known protein complexes. Many of the reported cancer synthetic lethalities fall into this category [33][34][35][36][37].…”
Section: Prioritizing Paralog Pairs Most Likely To Exhibit Synthetic mentioning
confidence: 99%
“…It is well established that SA1 and SA2 have overlapping as well as unique functions (35,73,74). Cohesin SA1 plays a more prominent role than SA2 in the regulation of gene expression (74). One major structural difference between SA1 and SA2 proteins is found in the first 75 amino acids of their N-terminal domains (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, we may be able to indirectly target Sp1 in cancer by identifying and exploiting its synthetic lethal dependencies. Several recent studies have identified synthetic lethal interactions during mitosis in other contexts (Oser et al, 2019;van der Lelij et al, 2017).…”
Section: Discussionmentioning
confidence: 99%